The PREVALENCE OF CLINICAL SPECTRUM OF INHERITED METABOLIC DISORDERS IN INFANTS AND CHILDREN AT A TERTIARY CARE HOSPITAL IN RAWALPINDI, PAKISTAN: Clinical manifesttaions of IMDs. - Batool, Ayesha; Zaman, Saeed; Ayub, Ammara; Bilal, Kulsum; Malik, Qudratullah (Pakistan Armed Forces Medical Journal, 2020)
Objective:  To determine the frequency of a wide range of clinical presentations of inherited metabolic disorders diagnosed in infants and children at a tertiary care hospital in Rawalpindi, Pakistan.Study Design: Cross sectional studyPlace and Duration of Study: MH Rawalpindi, from June 2015 till June 2016.Material and Methods:  64 children diagnosed with metabolic disorders, reporting to the MH Rawalpindi, were enrolled in the study. History was taken with special reference to family history, consanguineous marriage, sibling’s death and clinical manifestations. Thorough physical examination was done in every patient to find out the clinical signs present. All the data was recorded on a proforma. SPSS-20 version was used to derive the results and p-value of